The Living Qur’an: Ethnographic Study and Understanding of Al-Isra’: 9 in Urban Communities - Nur Rihladhatul 'Aisy Sayoga (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research presents the understanding and application of the values of the Qur’an, specifically Al-Isra’: 9, and its influence on the lifestyles of individuals who migrate to big cities for work or education. The ethnographic study was conducted in urban communities in the cities of Jakarta and Yogyakarta, involving 2o workers and 20 students. The research was conducted using qualitative methods, including participatory observation, questionnaires and in-depth interviews to understand the adaptation strategies of individuals in urban life, while maintaining their religious beliefs. The research results show that despite are many challenges, such as hectic schedules, unsupportive work or academic environments, and social pressure to adapt to an urban lifestyle, individuals still try to carry out religious practices. Facilities and technology play a crucial role in supporting these practices, and the active support of religious communities proves highly beneficial in maintaining Qur’anic values. This research identifies affective adaptation strategies and provides practical recommendation to help individuals maintain the values of the Qur’anic in a dynamic environment, such as good time management and participation in community activities.